Rectal injury associated with insertion of a vaginal delineator tube during total laparoscopic hysterectomy: A case report and review of the literature - Satoshi Asai; Hitoshi Ishimoto; Satsuki Okuno; Akira Yabuno; Hironori Asada; Bao-Liang Lin (Wolters Kluwer Medknow Publications, 2014)
We present a case of rectal injury during total laparoscopic hysterectomy (TLH) associated with placement of a vaginal delineator tube. The patient was a 43-year-old virgin woman who presented with hypermenorrhea secondary to a large submucosal leiomyoma and underwent TLH. On insertion of a vaginal delineator tube, the boundary between the posterior vaginal fornix and the rectum was misjudged and the rectum was cut. The patient subsequently required transvaginal repair and a temporary ileostomy. With more widespread use of a vaginal delineator tube in TLH, sharing this rare experience with our colleagues will minimize such a complication.